THE UTILIZATION OF DIGITAL MARKETING STRATEGIES TO IMPROVE TILAPIA MARKETING AT MERUYUNG FISH FARM - Fitri Wahyuni; Irsyada Ahmad Althaf Farih; Riki Hendra Purba; James Julian; Miguna Astuti; Fathin Muhammad Mahdhudhu; Elvi Armadani (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
The main challenges faced by freshwater fish farming MSMEs, such as Meruyung Fish Farm in Depok, are the efficiency of the aeration system and conventional marketing management. This results in low productivity, high operational costs, and minimal market competitiveness. To overcome these problems, the community service team implemented two strategic solutions: technology and innovation, as well as improvements in marketing management. The technological approach focused on the design and application of Superchargers as an energy-efficient aeration system. This technology can effectively increase dissolved oxygen levels, which positively impacts fish growth, feed efficiency, and survival rates. Previous research shows that one Supercharger unit can aerate up to 10 pounds, significantly reducing energy consumption compared to conventional methods. On the other hand, marketing management improvements were carried out through business incubation and digital marketing. These activities include training in processed product diversification, promotional content creation, social media and e-commerce management. Thus, this program not only improves productivity from a technical perspective but also strengthens the business capacity of partners to be more competitive and sustainable in the market. The expected outcome is a 20% increase in the production capacity and sales turnover of partners.